1986
DOI: 10.1099/00221287-132-12-3309
|View full text |Cite
|
Sign up to set email alerts
|

Catabolite Repressive Effects of 5-Thio-D-glucose on Saccharomyces cerevisiae

Abstract: The effect of the glucose analogue 5-thio-D-glucose (5TG) on the yeast Saccharomyces cerevisiae was studied. Derepression of mitochondrial respiratory chain cytochromes, alcohol dehydrogenase (isoenzyme II), NADH dehydrogenase and maltase was inhibited by 0.5-2 mM-5TG. Growth rate was only slightly affected. Ethanol was efficiently produced with 2 mM-5TG in medium initially containing 0.25% glucose. Mutants resistant to the growth inhibitory effects of 5TG on glycerol medium showed resistance to the catabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Yet, this difference to the use of commercial yeasts was not found in fermentations of plum or pear mashes (this work; 4 ). It can be concluded that cherry mashes contain some growth inhibitory compound(s) like sulfur compounds (forming because of acidifying with sulfuric acid), which show antifungal activity to which the laboratory strain may be more sensitive ( , ). In this context, an inadequate supply of nitrogen can crucially influence the growth of the yeast and initiate malolactic fermentation ().…”
Section: Discussionmentioning
confidence: 99%
“…Yet, this difference to the use of commercial yeasts was not found in fermentations of plum or pear mashes (this work; 4 ). It can be concluded that cherry mashes contain some growth inhibitory compound(s) like sulfur compounds (forming because of acidifying with sulfuric acid), which show antifungal activity to which the laboratory strain may be more sensitive ( , ). In this context, an inadequate supply of nitrogen can crucially influence the growth of the yeast and initiate malolactic fermentation ().…”
Section: Discussionmentioning
confidence: 99%
“…The glucose analogue 5-thioglucose is known to induce glucose repression in S. cerevisiae, yet cannot be metabolized after it has been taken up by the cell (Egilsson et al, 1986). Consequently, a wild-type S. cerevisiae strain will not be able to grow on medium containing 5-thioglucose plus another carbon source, such as sucrose, galactose, maltose or ethanol, since the required pathways and enzymes are repressed.…”
Section: Glucose Repression Through Hxk2 Revisitedmentioning
confidence: 99%
“…As glucose will not only act as an inducer of glaA-promoter controlled gene expression but is also readily metabolized two different types of non-metabolizable glucose analogs (5-thio-glucose and 2-deoxyglucose) were used to study their concentration-dependent effects on glaA-promoter controlled gene expression in the presence of the non-inducing and non-repressing carbon substrate citrate. Both analogs exhibit growth-inhibiting effects at higher concentrations and have been widely used to isolate glucose derepressed yeasts and filamentous fungi after chemical or UV mutagenesis (Egilsson et al, 1986;Fiedurek et al, 1987;Ghosh et al, 1991;Matosic et al, 1996).…”
Section: Induction and Repression Of Glaa-promoter Controlled Gene Exmentioning
confidence: 99%